2015
DOI: 10.1016/j.nlm.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal nociceptive stimulation results in deficits of spatial memory in male rats

Abstract: Prematurely-born infants are exposed to multiple invasive procedures while in the intensive care unit. Newborn rats and humans have similar behavioral responses to noxious stimulation. Previous studies have shown that early noxious stimuli may alter dentate gyrus neurogenesis and the behavioral repertoire of adult rats. We evaluated the late effects of noxious stimulation administered during different phases of development on two spatial memory tests; object recognition (OR) and Morris water maze (WM) tests. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
8
0
3
Order By: Relevance
“…There is abundant evidence from animal studies that repetitive pain and/or stress in early life can alter both the structure and function of the developing brain and, consequently, alter pain and/or stress responses in adulthood. Amaral et al (2015) have demonstrated that inflammatory nociceptive stimulation in the first postnatal week reduces the time spent exploring novel objects and affects long‐term memory in male animals. Mooney‐Leber et al (2018) showed that both neonatal isolation and repeated pain altered the corticosterone levels and the glutamate levels within the frontal cortex and hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is abundant evidence from animal studies that repetitive pain and/or stress in early life can alter both the structure and function of the developing brain and, consequently, alter pain and/or stress responses in adulthood. Amaral et al (2015) have demonstrated that inflammatory nociceptive stimulation in the first postnatal week reduces the time spent exploring novel objects and affects long‐term memory in male animals. Mooney‐Leber et al (2018) showed that both neonatal isolation and repeated pain altered the corticosterone levels and the glutamate levels within the frontal cortex and hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the neurogenic effects of early repetitive noxious experiences are limited to PND 1 (postnatal day 1) and PND 8 (Malheiros et al, 2014; Amaral et al, 2015; den Hoogen et al, 2017) and that repetitive stimulation of the nociceptive system in a rat model using needle pricks in the hind‐paw closely mimics the clinical situation of infants in NICU (den Hoogen et al, 2017). In contrast, repeated procedural pain during the first 14–15 days of life in rat pups resulted in impairment of long‐term memory (Nuseir et al, 2017) and sensory and motor functions (Sanada et al, 2014; Carmo Ede et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory pain caused by the intra-plantar injection of carrageenan (1%) on the day of birth, P0, resulted in spatial memory deficits also in adult rats (Henderson et al, 2015), and dysregulated the HPA axis (Victoria et al, 2013). Complete Freund's adjuvant on P1 did not affect short-or long-term memory in male or female rats on P60, but resulted in spatial learning deficits in males (Amaral et al, 2015). Therefore, although there are some inconsistencies, in general early experiences of painful injury can disrupt adult spatial learning/memory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Complete Freund's adjuvant (CFA) is used as a model of persistent hind paw peripheral inflammation, that showed that, as adults, the animals had altered responses to sensory stimulation (Ruda, Ling, Hohmann, Peng, & Tachibana, 2000). So, by means of a subcutaneous injection of CFA in neonatal rat pups, we have been able to study the long‐term consequences of such early activation of the nociceptive system selectively, on behavior and neurogenesis (Amaral et al., 2015; Leslie et al., 2011; Lima et al., 2014; Malheiros, Lima, et al, 2014; Negrigo, Medeiros, Guinsburg, & Covolan, 2011) without concurrent tactile afferent information. In this study, we aimed to use this neonatal rat model investigate whether inflammatory painful stimulation in the first postnatal week on postnatal day 1 or 8 (P1 or P8) could promote long‐term effects on pain‐related pathways within the CNS, when the same noxious stimulus is applied in adulthood.…”
Section: Introductionmentioning
confidence: 99%